Evolutionary history of the DNA repair protein, Ku, in eukaryotes and prokaryotes - Sadikshya Rijal; Ashmita Mainali; Sandesh Acharya; Hitesh Kumar Bhattarai (PLoS ONE, 2025)
Ku is essential in non-homologous end-joining (NHEJ) across prokaryotes and eukaryotes, primarily in double-stranded breaks (DSBs) repair. It often presents as a multi-domain protein in eukaryotes, unlike their prokaryotic single-domain homologs. We systematically searched for Ku proteins across different domains of life. To elucidate the evolutionary history of the Ku protein, we constructed a maximum likelihood phylogenetic tree using Ku protein sequences from 100 representative eukaryotic, prokaryotic, and viral species. The resulting tree revealed a common node for eukaryotic Ku proteins, while viral and prokaryotic species clustered into a distinct clade. Our phylogenetic analysis reveals that the common ancestry of Ku70 and Ku80 likely resulted from a gene duplication event in the ancestral eukaryote. This inference is supported by BLASTp results, which indicate a close resemblance between archaeal Ku and eukaryotic Ku, particularly Ku70. The presence of both Ku protein paralogs in the Discoba group further supports the hypothesis that the gene duplication occurred early in eukaryotic evolution. It is plausible that archaea, which may have acted as intermediaries for Ku transfer, subsequently lost the Ku protein. Nonetheless, the extensive horizontal transfer of Ku among prokaryotes and its relatively higher prevalence in bacteria complicates our understanding of how Ku protein was inherited by early-branching eukaryotes.